THE EFFECT OF TIME VARIATION ON THE ACTIVATED CARBON ADSORPTION ABILITY OF BANANA STEM WASTE (MUSA PARADISIACA L.) AGAINST BENZENE - Laupa, Siti Aisyah; Alimuddin, Alimuddin; Sitorus, Saibun (Jurusan Kimia FMIPA UNMUL, 2019)
The research was conducted about the adsorption ability of activated carbon from banana trunk waste (Musa paradisiaca L.) toward benzene. The purpose of this research was to find out the characteristics and the adsorption ability of activated carbon from banana trunk waste in the form value of capacity in adsorption process. In this research, the production of activated carbon from banana trunk waste through stages of preparation and carbonization that was activated using H3PO4 solution. Then the carbon with SNI No. 06-3730-1995 was characterized and using Scanning ElectronMicroscopy (SEM) to find out the morphology of adsorbent. The result of analysis of SEM characteristics of activated carbon was the pores that were formed became larger. In addition, another analysis that was obtained namely 4.6% moisture content; 22.42% ash content; 24.14%volatile matter content; 48.74% bonded carbon content; 347.73 m2/g surface area and adsorption with I2 176.5 mg/g. At the optimum variations of the time of adsorption capacity value is equal1.692 mg/g.